Functional traits and adaptive capacity of European forests to climate change - Bussotti, Filippo; Pollastrini, Martina; Holland, Vera; Brüggemann, Wolfgang (Environmental and Experimental Botany, 2014)
Increasing temperatures and drought risks through climate change are expected to have several consequences for European forests. Adaptive strategies may include: (i) persistence of the current forest types, thanks to the acclimatization to local conditions and to phenotypic plasticity of the populations; (ii) evolution, or local adaptation, i.e., change in genotype (frequencies) within the same species due to environmental pressure. It is favored by large within population diversity and (when possible) gene flow among populations; (iii) migration and substitution of species; and (iv) extinction of populations with low ecological plasticity, especially at the edges of their distribution or in the case of isolated (relict) populations. Because of the economic and ecological relevance of forests, it is of fundamental importance to apply appropriate forest management to make forests able to cope with the new environmental conditions. This may include changes in the composition and structure of forest stands, selection of adapted provenances of the most important European tree species or, if this is regarded as insufficient, assisted migration (i.e., the use of species suitable for the future climatic conditions) and, alternatively, substitution of native with non native species. The intraspecific (genetic and phenotypic) variability at a given site has been proven to be often higher than the variability among sites. Species with a large distribution range are supposed to have a wide variety of genotypes, allowing them to be adapted to different environmental conditions. Genetic variability and phenotypic plasticity are the key factors for the identification of useful tree genotypes for future forestation programs. Adaptation to drought, i.e., the probably most important future abiotic risk factor for forestry, can be reflected in variation of key functional traits (FT), at morphological, physiological and phenological level. FT utilized to screen for adapted genotypes in common gardens and provenance trials include growth, survival, leaf flushing and senescence, foliar features as leaf mass per area and nitrogen content, water use efficiency (e.g., estimated by analysis of the stable carbon isotopes, d13C) chlorophyll content, photosystem II functioning, and photosynthetic capacity under water shortage. Current modeled simulation of future forest distribution suggests the expansion of forests at the highest latitudes and altitudes, alongside with a reduction in the hottest and driest Mediterranean regions of South Europe. The general expectations, however, may be disproved especially at a regional level, by factors unexpected or not well known, such as possible extreme climatic events and increased roles of parasites/diseases (with negative effects), or high capacity of forest persistence or adaptation (with positive effects). Natural migration and species substitution can be hampered by co-factors of climate change, such as forest fragmentation and increased frequency and intensity of forest fires.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Adaptation; Extinction; functional traits; Local evolution; migration; Phenotypic plasticity; Phenotyping; provenances

DESERTIFICATION–A NEW SECURITY CHALLENGE FOR THE MEDITERRANEAN? Policy agenda for recognising and coping with fatal outcomes of global - Brauch, H. G. (Desertification in the Mediterranean Region. A Security …, 2006)
Desertification (representing soil degradation) is one of the three nature-induced (climate change, hydrological cycle) and of three primarily human-induced challenges (population growth, urbanisation and food) of global environmental change. These six components closely interact and contribute to fatal outcomes: primarily to extreme weather events and hydro-meteorological disasters (drought, flash floods, storms) and environmentally-induced migrations. These two fatal outcomes may have – in some cases – societal repercussions that may trigger or contribute to domestic, regional and international crisis and conflicts and thus they may become an issue of both human, societal, national and international security. To illustrate the causal linkages: for example in Morocco in the 1980s and 1990s, the following chain of events could be observed: severe drought, increase in food prices, hunger riots, general strikes, the police and armed forces interfered to repress these violent upheavals and subsequently hundreds of casualties could be deplored. These cases were not listed as a conflict in the relevant conflict data bases. The paper is organised in three parts: In the first part, the complex casual interactions among six factors of global environment change, two fatal outcomes and three societal repercussions: crises, conflicts and conflict avoidance, prevention and resolution will be discussed. In the second part, different security concepts will be reviewed that may be of relevance for dealing with desertification as a security issue. In the third part, possible security relevance pro-active political strategies will be considered, to avoid, and prevent that desertification issues can pose security challenges, and to contribute to a resolution of the desertification driven violence. 11
The following values have no corresponding Zotero field: periodical: Desertification in the Mediterranean Region. A Security …
Keywords: conflict; desertification; Drought; environmental degradation; environmental security; food security; Global change; human security; Land degradation; migration; natural disasters (voyant)

DESERTIFICATION–A NEW SECURITY CHALLENGE FOR THE MEDITERRANEAN? Policy agenda for recognising and coping with fatal outcomes of global - Brauch, H G (Desertification in the Mediterranean Region. A Security …, 2006)
Desertification (representing soil degradation) is one of the three nature-induced (climate change, hydrological cycle) and of three primarily human-induced challenges (population growth, urbanisation and food) of global environmental change. These six components closely interact and contribute to fatal outcomes: primarily to extreme weather events and hydro-meteorological disasters (drought, flash floods, storms) and environmentally-induced migrations. These two fatal outcomes may have – in some cases – societal repercussions that may trigger or contribute to domestic, regional and international crisis and conflicts and thus they may become an issue of both human, societal, national and international security. To illustrate the causal linkages: for example in Morocco in the 1980s and 1990s, the following chain of events could be observed: severe drought, increase in food prices, hunger riots, general strikes, the police and armed forces interfered to repress these violent upheavals and subsequently hundreds of casualties could be deplored. These cases were not listed as a conflict in the relevant conflict data bases. The paper is organised in three parts: In the first part, the complex casual interactions among six factors of global environment change, two fatal outcomes and three societal repercussions: crises, conflicts and conflict avoidance, prevention and resolution will be discussed. In the second part, different security concepts will be reviewed that may be of relevance for dealing with desertification as a security issue. In the third part, possible security relevance pro-active political strategies will be considered, to avoid, and prevent that desertification issues can pose security challenges, and to contribute to a resolution of the desertification driven violence. 11
Keywords: conflict; desertification; Drought; environmental degradation; environmental security; food security; Global change; human security; Land degradation; migration; natural disasters (voyant)

Quantifying components of risk for European woody species under climate change - OHLEMÜLLER, RALF; GRITTI, EMMANUEL S.; SYKES, MARTIN T.; THOMAS, CHRIS D. (Global Change Biology, 2006)
Estimates of species extinction risk under climate change are generally based on differences in present and future climatically suitable areas. However, the locations of potentially suitable future environments (affecting establishment success), and the degree of climatic suitability in already occupied and new locations (affecting population viability) may be equally important determinants of risk. A species considered to be at low risk because its future distribution is predicted to be large, may actually be at high risk if these areas are out of reach, given the species' dispersal and migration rates or if all future suitable locations are only marginally suitable and the species is unlikely to build viable populations in competition with other species. Using bioclimatic models of 17 representative European woody species, we expand on current ways of risk assessment and suggest additional measures based on (a) the distance between presently occupied areas and areas predicted to be climatically suitable in the future and (b) the degree of change in climatic suitability in presently occupied and unoccupied locations. Species of boreal and temperate deciduous forests are predicted to face higher risk from loss of climatically suitable area than species from warmer and drier parts of Europe by 2095 using both the moderate B1 and the severe A1FI emission scenario. However, the average distance from currently occupied locations to areas predicted suitable in the future is generally shorter for boreal species than for southern species. Areas currently occupied will become more suitable for boreal and temperate species than for Mediterranean species whereas new suitable areas outside a species' current range are expected to show greater increases in suitability for Mediterranean species than for boreal and temperate species. Such additional risk measures can be easily derived and should give a more comprehensive picture of the risk species are likely to face under climate change.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: dispersal; distance; distribution; distribution modelling; extinction risk; Forests; migration; range shifts

Quantifying components of risk for European woody species under climate change - OHLEMÜLLER, RALF; GRITTI, EMMANUEL S; Sykes, Martin T; THOMAS, CHRIS D (Global Change Biology, 2006)
Estimates of species extinction risk under climate change are generally based on differences in present and future climatically suitable areas. However, the locations of potentially suitable future environments (affecting establishment success), and the degree of climatic suitability in already occupied and new locations (affecting population viability) may be equally important determinants of risk. A species considered to be at low risk because its future distribution is predicted to be large, may actually be at high risk if these areas are out of reach, given the species' dispersal and migration rates or if all future suitable locations are only marginally suitable and the species is unlikely to build viable populations in competition with other species. Using bioclimatic models of 17 representative European woody species, we expand on current ways of risk assessment and suggest additional measures based on (a) the distance between presently occupied areas and areas predicted to be climatically suitable in the future and (b) the degree of change in climatic suitability in presently occupied and unoccupied locations. Species of boreal and temperate deciduous forests are predicted to face higher risk from loss of climatically suitable area than species from warmer and drier parts of Europe by 2095 using both the moderate B1 and the severe A1FI emission scenario. However, the average distance from currently occupied locations to areas predicted suitable in the future is generally shorter for boreal species than for southern species. Areas currently occupied will become more suitable for boreal and temperate species than for Mediterranean species whereas new suitable areas outside a species' current range are expected to show greater increases in suitability for Mediterranean species than for boreal and temperate species. Such additional risk measures can be easily derived and should give a more comprehensive picture of the risk species are likely to face under climate change.
Keywords: dispersal; distance; distribution; distribution modelling; extinction risk; Forests; migration; range shifts

Feeding behaviour of autumn passage migrants in north east Portugal - Ferns, Peter N. (Ringing & Migration, 1975)
IN THE SUMMER and autumn of 1973, a mist netting site in the sparsely wooded hill country of north east Portugal was continuously manned by members of the Iberian Ringing Group. The main objective was to study the increases in weight of trans-Saharan passerine migrants which use this particular area as a staging post on their southward journey (Mead 1968). These migrants arrive on the central Iberian plateau towards the end of a long, dry summer, at a time when conditions appear relatively inhospitable. Yet Willow Warblers* and Pied Flycatchers gain over 0.2 g/day in weight, while Whitethroats increase by over 0.4 g/day (C. J. Mead and B. R. Watmough in prep.). Though this is somewhat less than, for example, the 0.6 g/day gained by Whitethroats at Lake Chad, Nigeria, in preparation for the return journey to the Palaearctic in spring (Fry. Ash and FergusonLees 1970), it still suggests that reasonable food supplies are available. In order to determine the nature of the foods being taken by these migrants, a series of observations were made during late August and early September 1973 in association with mist-netting activities.
doi: 10.1080/03078698.1975.9673692doi: 10.1080/03078698.1975.9673692The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Feeding activity; Feeding habits (PG); migration; passerines